Establishment and functional characterization of an EGFR-amplified tumoroid from squamous cell carcinoma of unknown primary - Miki Iwai; Etsuko Yokota; Takuro Yukawa; Kizuki Matsumoto; Takashi Urano; Kazutaka Nakashima; Hiroyoshi Doihara; Nagio Takigawa; Hideyo Fujiwara; Takashi Akiyama; Minoru Haisa; Yoshio Naomoto; et al. (Human Cell, 2026)
Carcinoma of unknown primary (CUP) remains a clinically challenging malignancy with limited treatment options and poor prognosis. Although genomic profiling has identified potentially actionable alterations, optimal therapeutic strategies are often unclear. Here, we report the establishment and characterization of a patient-derived tumoroid from an EGFR -amplified CUP and evaluate its utility as a functional model for therapeutic assessment. The patient-derived tumoroid (PDT-CUP#1) was successfully established from resected tumor tissue and maintained in long-term culture. Whole-exome sequencing demonstrated genomic concordance between the PDT-CUP#1 and the original tumor. Quantitative PCR and fluorescence in situ hybridization confirmed EGFR amplification. Xenograft tumors derived from PDT-CUP#1 recapitulated the histopathological features of the original lesion. Functional drug testing demonstrated differential sensitivity among EGFR-targeted agents. Whereas EGFR tyrosine kinase inhibition resulted in modest growth suppression, anti-EGFR monoclonal antibodies exhibited moderate antitumor effects, and an EGFR-targeted antibody–drug conjugate showed the most pronounced growth inhibition. Notably, the therapeutic sensitivity observed in the tumoroids was generally consistent with the patient’s clinical response to platinum-based chemotherapy combined with necitumumab. These findings demonstrate that a CUP-derived tumoroid can be successfully established while preserving the key molecular and pathological features of the original tumor. This model provides a platform for functional evaluation of therapeutic vulnerabilities and offers proof-of-concept for integrating patient-derived tumoroids into therapeutic decision-making in CUP.